Artikel tentang Campur Kode Mahasiswa STAB Maitreyawira - Yadi Sutikno (STAB Maitreyawira, 2020)
Based on observations found that there are not many studies that can explain clearly about the factors that cause students to mix codes. Though the factors that cause students to mix codes are important to be known by language lecturers and for lecturers who teach on campus. Based on these observations it is necessary to conduct research on code mixing. Research on code mixing in the study will be conducted at STAB Maitreyawira with a sample of research that is STAB Maitreyawira students. The method in this study is a qualitative method. The languages ​​used in mixing codes at STAB Maitreyawira are Indonesian, Malay, Mandarin, English, Mandarin and Jakarta dialect Malay. Then the students understand the code mix they do. Then, the factors that cause code mixing among STAB Maitreyawira students are as follows: the desire to look great, the topic or topic, the situation factor, the language factor on YouTube, the language factor on Facebook, and the factors to be more familiar with friends.